River Rehabilitation Criteria: Stream Rehabilitation Concepts, Guidelines and Examples - Julien, Pierre Y. (2005)
Streams and rivers vary in character from place to place: from headwaters to mouth and from region to region. They also change over time, rapidly during floods and gradually over much longer periods. These phenomena are part of urban as much as natural rivers, and must be understood if we are to achieve and sustain urban renewal. In their natural state, river corridors offer many benefits. These include clean water, productive fisheries, a diverse range of plants and wide life in and out of water, navigation routes, and flood storage reservoirs (flood plains). But as rivers and their valleys become altered through urbanization, some of these benefits are lost and others become degraded and more costly to sustain.